A History of Male Psychological Disorders in Britain, 1945-1980. - Haggett, Alison. (Mental Health in Historical Perspective Series, 2015)
This book is open access under a CC BY license and explores the under-researched history of male mental illness from the mid-twentieth century. It argues that statistics suggesting women have been more vulnerable to depression and anxiety are misleading since they underplay a host of alternative presentations of 'distress' more common in men.